Carbon-based confined bimetallic single-atom catalytic materials and their application in removing perchlorate from drinking water
Through carbon-based limited-domain bimetallic single-atom catalytic materials and formic acid strengthening treatment, the problems of low efficiency and high cost of perchlorate removal in drinking water are solved, and efficient and economical perchlorate removal is achieved, meeting national health standards and Reduced the risk of secondary pollution.
Patent Information
- Application Number
- CN202411414238.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The prior art has low efficiency, high cost, complex operation in drinking water, and the risk of secondary pollution, making it difficult to meet national health standards.
Using carbon-based limited-domain bimetallic single-atom catalytic material, through metal-nitrogen coordination structure design, use metal atoms such as Mo, Mn, Cu, Ni to achieve efficient adsorption and reduction of perchlorate, combined with formic acid strengthening treatment, to improve the material's Adsorption and anti-interference ability.
It significantly improves the removal efficiency of perchlorate, reduces operating costs, simplifies processing procedures, ensures the stability and economicality of long-term operations, and achieves a perchlorate content of less than 70 μg/L, reducing 2 Secondary pollution risk.
Smart Images

Figure CN118904392B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water purification technology, specifically carbon-based confined bimetallic single-atom catalytic materials and their application in removing perchlorate from drinking water. Background Technology
[0002] perchlorate ( Perchlorate, a compound playing a vital role in industry, is widely used as a strong oxidant in fireworks manufacturing, the arms and aerospace industries. It also serves as an essential additive in the production of leather tanning agents, lubricants, rubber products, and magnesium batteries. Furthermore, it participates in the synthesis of certain chemicals, acting as a catalyst. However, despite its wide applications, the use and emission of perchlorate have caused environmental pollution problems, posing potential risks to ecosystems and human health.
[0003] Perchlorate not only originates from industrial production but is also part of the natural chlorine cycle, competitively inhibiting the uptake and use of iodine by thyroid follicular epithelial cells. Potential health effects include suppressing thyroid function, disrupting metabolism and growth, and potentially causing changes in cell structure and abnormal gene expression, posing a threat to reproductive health and embryonic development. In recent years, perchlorate emitted into the environment from human production activities and naturally occurring perchlorate have widely participated in the ecological cycle and entered the food chain through it. Domestic and international studies have detected perchlorate in various foods, including drinking water, beverages, wine, agricultural products, and dairy products. To address this issue, my country implemented the "Standards for Drinking Water Quality" (GB5749-2022) on April 1, 2023, including perchlorate in its regulations and setting a standard limit of 70 μg / L.
[0004] To reduce the perchlorate content in drinking water, the industry has explored the application of various treatment technologies to achieve effective perchlorate removal. Currently, perchlorate treatment technologies in drinking water mainly include physical, chemical, and biological methods. Physical methods include activated carbon adsorption, ion exchange, and membrane separation technology. Activated carbon adsorption technology has advantages such as high treatment efficiency and simple operation, and is one of the earliest water treatment technologies. However, activated carbon typically has a low adsorption capacity and poor resistance to interference. Furthermore, surfactant treatment increases treatment costs and can cause secondary pollution. Membrane separation technology plays an important role in removing perchlorate from drinking water. Perchlorate can be removed through reverse osmosis and nanofiltration, but the production cost of nanofiltration and reverse osmosis membranes is expensive, and they are mainly used in small-scale drinking water plants. Microbial degradation and reduction technology for perchlorate is a relatively mature and effective technology. Microorganisms can utilize perchlorate for respiration under the action of a multi-factor metalloenzyme system, thereby reducing perchlorate. However, biological methods are complex, difficult to operate, require a large area, and have long operating times. They also pose secondary pollution risks during the process, thus limiting their application in drinking water treatment. Chemical methods typically reduce perchlorate to harmless chloride ions through oxygen atom transfer reactions and hydrogenation deoxygenation reactions. However, the steric hindrance of perchlorate makes it difficult for chloride atoms to directly accommodate the extra electrons of conventional reducing agents to reduce its oxidation state. Furthermore, perchlorate exhibits redox kinetic inertness, weak coordination ability, and weak nucleophilicity in dilute aqueous solutions at room temperature and pressure, resulting in a high activation energy for the reduction of perchlorate to chloride ions. To better degrade perchlorate, it is usually necessary to introduce H2 into the reaction system or provide high temperatures.
[0005] It is evident that the removal of perchlorate from drinking water still faces challenges, and there is an urgent need to develop more efficient, faster, and more cost-effective treatment technologies. Summary of the Invention
[0006] To address the shortcomings of existing perchlorate removal technologies in drinking water, such as limited adsorption capacity, complex reaction condition control, insufficient anti-interference ability, low reusability, and unsatisfactory practical application results, this invention proposes an innovative solution: a carbon-based confined bimetallic single-atom catalytic material. This material exhibits excellent adsorption and reduction properties, significantly improving perchlorate removal efficiency. The application of this technology can reduce the perchlorate content in drinking water to below the national drinking water hygiene standard (below 70 μg / L) in a short time, while simplifying the treatment process and reducing operating costs. Furthermore, the material's stability and recyclability lower long-term operating costs, improving the practicality and economy of water treatment technology.
[0007] The first technical problem solved by this invention is to provide a carbon-based confined bimetallic single-atom catalytic material, wherein the catalytic material has a carbon-based framework and nitrogen atoms as coordinating atoms, and specific metal atoms are dispersed and fixed in single-atom form through a metal-nitrogen (Me-N) coordination structure; wherein the metal atoms are any two of Mn, Cu, Ni and Mo.
[0008] In some preferred embodiments, the metal atoms are any combination of Mo-Mn, Mo-Cu, Mo-Ni, and Mo-Mo.
[0009] The second technical problem solved by this invention is to provide a method for preparing a carbon-based confined bimetallic single-atom catalytic material, the specific steps of which are as follows:
[0010] (1) Preparation of precursor solutions: Using dimethylformamide as solvent, prepare solution A containing zinc nitrate and the first metal salt, and solution B containing 2-methylimidazole;
[0011] (2) Growth of nanocrystals: Mix solutions A and B, keep warm under sealed conditions to promote the growth of nanocrystals with metal-nitrogen coordination structure, remove impurities by centrifugation and washing, and vacuum dry the precipitate to obtain nanocrystals;
[0012] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals are heated to 900~1200℃ for a first calcination;
[0013] (4) Pickling: The material after one calcination is pickled, filtered, washed, and vacuum dried to obtain carbon-based material;
[0014] (5) Introduction of the second metal: The carbon-based material is fully dispersed in isopropanol solution, the second metal salt and melamine are added, ultrasonically dispersed, recovered, dried and the particles are collected;
[0015] (6) Secondary calcination: Under a nitrogen atmosphere, the particles are heated to 800~1000℃ for secondary calcination to obtain carbon-based confined bimetallic single-atom catalytic material.
[0016] In a preferred embodiment, the molar ratio of zinc nitrate, the first metal salt, and 2-methylimidazole in step (1) is 10~30:1:20~60.
[0017] In a preferred embodiment, the molar ratio of the second metal salt, 2-methylimidazole, in step (5) is 1:1~5.
[0018] The third technical problem solved by this invention is to provide a method for removing perchlorate from drinking water, wherein the method uses the above-mentioned carbon-based confined bimetallic single-atom catalytic material as a catalyst to remove perchlorate from drinking water.
[0019] In some specific embodiments, when the carbon-based confined bimetallic single-atom catalytic material is used as a catalyst, it is in the form of powder, granules, or supported on a carrier.
[0020] In a preferred embodiment, the process employs formic acid enhancement treatment.
[0021] In one specific embodiment, the formic acid enhancement treatment involves sequentially adding a catalyst and a certain concentration of formic acid to a reactor containing a water sample to be purified, stirring thoroughly, controlling the residence time of the water sample in the reactor to be 5 to 30 minutes, followed by filtration and catalyst recovery.
[0022] In a preferred embodiment, the concentration of formic acid is 0.5~2 mM.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] This invention provides an innovative carbon-based confined bimetallic single-atom material for the targeted removal of perchlorate from drinking water. Unlike other common pollutants, perchlorate is an inorganic anion. The catalytic material designed in this invention is based on the properties and spatial size of perchlorate, directionally constructing a catalytic material with abundant nano-confined pore structures and a high specific surface area, achieving highly efficient adsorption and reduction of perchlorate. Furthermore, the nanoscale confined adsorption characteristics effectively isolate large molecules in the wastewater, reducing competition for adsorption sites and further improving the material's utilization rate and removal efficiency.
[0025] The transition metal-nitrogen coordination structure (Me-N) within the material not only increases the number of active sites, but the Me-N coordination environment also imparts positive charge to the metal atomic sites, enhancing their affinity for the negatively charged ClO4. - The electrostatic attraction significantly improves the directional adsorption efficiency of perchlorate. Furthermore, Mo, a single-atom metal with good biocompatibility and catalytic activity, was specifically selected, utilizing the interaction between Mo atoms and ClO4. - The efficient interfacial bonding ability between O atoms enhances the adsorption performance of the material.
[0026] In the process of purifying drinking water, a formic acid-enhanced treatment is employed to optimize the surface charge of the material and further improve its adsorption capacity for perchlorate. The presence of formic acid causes the metal single-atom sites to carry more positive charges, thus strengthening the adsorption of ClO4. - The electrostatic attraction of formic acid simultaneously promotes the formation of chemical bonds, enhancing the material's chemisorption performance. This strengthening treatment improves the material's resistance to interference under complex water quality conditions, ensuring high efficiency and stability in practical applications. Through the strengthening effect of formic acid, removal efficiency is improved, while also enhancing the material's environmental adaptability and practicality.
[0027] The catalytic material of this invention requires a low dosage, has a stable structure, and is a solid material that is easy to transport and store. This not only saves on technical costs but also reduces the potential risk of secondary pollution, ensuring the safety of the technology. Furthermore, the material exhibits high removal efficiency and rapid reaction capability, effectively removing even high concentrations of perchlorate with a short residence time and simple operation. The solid material is easily separated and recovered after deactivation, demonstrating excellent cycle stability and resistance to deactivation. Even after repeated use and regeneration, it maintains highly efficient adsorption performance, providing an economical and feasible solution for practical perchlorate removal. Attached Figure Description
[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0029] Figure 1 The image shows a scanning electron microscope (SEM) image of the Mn-Mo-NC material prepared in Example 1. Detailed Implementation
[0030] This invention discloses a carbon-based confined bimetallic single-atom catalytic material and its application in the removal of perchlorate from drinking water.
[0031] It should be understood that the expression “one or more of…” individually includes each of the objects described after the expression, as well as various different combinations of two or more of the described objects, unless otherwise understood from the context and usage. The expression “and / or” combined with three or more described objects should be understood to have the same meaning, unless otherwise understood from the context. The terms “comprising,” “having,” or “containing,” including the use of their grammatical synonyms, should generally be understood to be open-ended and non-restrictive, e.g., not excluding other undescribed elements or steps, unless specifically stated otherwise or otherwise understood from the context.
[0032] It should be understood that the order of the steps or the order in which certain actions are performed is not important as long as the invention remains operational. Furthermore, two or more steps or actions can be performed simultaneously.
[0033] Furthermore, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as precisely as possible. However, any value inevitably contains standard deviations due to individual test methods. Therefore, unless explicitly stated otherwise, it should be understood that all ranges, quantities, values, and percentages used in the present invention are modified with the word "approximately". Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a specific value or range.
[0034] Unless otherwise expressly stated, all percentages described in this invention are percentages by mass.
[0035] The first technical problem this invention aims to solve is to propose a carbon-based confined bimetallic single-atom catalytic material. This catalytic material uses a carbon-based framework and nitrogen atoms as coordinating atoms, achieving the dispersion and fixation of specific metal atoms in single-atom form through a metal-nitrogen (Me-N) coordination structure.
[0036] Any two of manganese (Mn), copper (Cu), nickel (Ni), and molybdenum (Mo) are selected as the catalytic material. The selection of these metal atoms is based on the characteristics of perchlorate to achieve the best catalytic removal effect.
[0037] In some embodiments, the two metal atoms selected are Mn-Mo, Mn-Ni, Mo-Cu, Mo-Ni, Cu-Ni, and Mo-Mo.
[0038] In particular, when molybdenum (Mo) is used as one of the metal atoms, the prepared catalytic material exhibits excellent performance in the reduction and purification of perchlorate. Molybdenum exists in nature in multiple oxidation states, such as molybdenum (O), molybdenum (III), molybdenum (IV), molybdenum (V), and molybdenum (VI), which gives it a significant interfacial electronic regulation effect, facilitating the generation of positive potential points at the material interface and enhancing its electrostatic adsorption of perchlorate. Furthermore, the multiple oxidation states of Mo facilitate valence electron transfer between Mo and O atoms, resulting in high activity in the reduction reaction.
[0039] In some preferred embodiments, the two metal atoms selected are any combination of Mo-Mn, Mo-Cu, Mo-Ni, and Mo-Mo.
[0040] The second technical problem solved by this invention is to provide a method for preparing a carbon-based confined bimetallic single-atom catalytic material, the specific steps of which are as follows:
[0041] (1) Preparation of precursor solutions: Using dimethylformamide as solvent, prepare solution A containing zinc nitrate and the first metal salt, and solution B containing 2-methylimidazole;
[0042] (2) Growth of nanocrystals: Mix solutions A and B, keep warm under sealed conditions to promote the growth of nanocrystals with metal-nitrogen coordination structure, remove impurities by centrifugation and washing, and vacuum dry the precipitate to obtain nanocrystals;
[0043] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals are heated to 900~1200℃ for a first calcination;
[0044] (4) Pickling: The material after one calcination is pickled, filtered, washed, and vacuum dried to obtain carbon-based material;
[0045] (5) Introduction of the second metal: The carbon-based material is fully dispersed in isopropanol solution, the second metal salt and melamine are added, ultrasonically dispersed, recovered, dried and the particles are collected;
[0046] (6) Secondary calcination: Under a nitrogen atmosphere, the particles are heated to 800~1000℃ for secondary calcination to obtain carbon-based confined bimetallic single-atom catalytic material.
[0047] In a preferred embodiment, the molar ratio of zinc nitrate, the first metal salt, and 2-methylimidazole in step (1) is 10~30:1:20~60.
[0048] In a preferred embodiment, the molar concentration of the first metal salt in solution A in step (1) is 0~20 mM;
[0049] In a preferred embodiment, the molar concentration of 2-methylimidazole in solution B of step (1) is 30~1200mM;
[0050] In some specific embodiments, the first metal salt is one of manganese acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate, and molybdenum acetate.
[0051] In one specific implementation, in step (2), solution A is slowly added dropwise to solution B while stirring to mix the two solutions evenly.
[0052] In one specific implementation, in step (2), the heat preservation temperature is 110~130℃ and the heat preservation time is 23~25 hours. This temperature environment is conducive to the continuous growth of nanocrystals.
[0053] In one specific implementation, in step (2), the centrifugation parameters are 8000 r / min, 25℃, and 10 min.
[0054] In one specific implementation, in step (2), anhydrous ethanol is used as the washing solution.
[0055] In one specific implementation, in step (2), the temperature of vacuum drying is 60°C.
[0056] In one specific embodiment, in step (3), the first calcination is carried out under a protective atmosphere, with the temperature increased to 1100°C at a rate of 3~7°C / min and held for 0.5~1.5 hours.
[0057] In one specific embodiment, in step (4), the acid washing process involves continuously stirring the calcined nanocrystals in 0.3~1M H2SO4 at 50~90℃ for 3~8 hours.
[0058] In some specific embodiments, in step (5), the second metal salt is one of manganese chloride, copper chloride, nickel chloride, and molybdenum chloride.
[0059] In a preferred embodiment, the molar ratio of the second metal salt to melamine in step (5) is 1:5.
[0060] In one specific implementation, in step (6), the secondary calcination is performed by heating to 900°C at a rate of 3~7°C / min and holding for 2.5~3.5 hours.
[0061] The third technical problem solved by this invention is to provide a method for removing perchlorate from drinking water, wherein the method uses the above-mentioned carbon-based confined bimetallic single-atom catalytic material as a catalyst to remove perchlorate from drinking water.
[0062] The specific method involves directly adding the catalytic material into the water treatment system, utilizing its excellent adsorption and catalytic properties to achieve rapid removal of perchlorate.
[0063] In a preferred embodiment, the dosage of the catalyst is 100 mg / L to 1000 mg / L.
[0064] In some specific embodiments, when the carbon-based confined bimetallic single-atom catalytic material is used as a catalyst, it is in the form of powder, granules, or supported on a carrier to efficiently remove perchlorate.
[0065] In some preferred embodiments, the carrier is activated carbon, ceramsite, silicate microspheres, etc.
[0066] In some specific implementations, the loading involves in-situ loading of carbon-based confined bimetallic single-atom catalytic material powder onto a support using a dry powder impregnation-calcination method.
[0067] In a preferred embodiment, the treatment process employs formic acid enhancement treatment, which further improves the adsorption and reduction efficiency of the catalytic material for perchlorate through the enhancing effect of formic acid.
[0068] In one specific embodiment, the formic acid enhancement treatment involves sequentially adding a catalyst and a certain concentration of formic acid to a reactor containing a water sample to be purified, stirring thoroughly, controlling the residence time of the water sample in the reactor to be 5 to 30 minutes, followed by filtration and catalyst recovery.
[0069] In a preferred embodiment, the formic acid concentration is 1.0 mM, a concentration range that can effectively enhance the removal performance of the catalytic material.
[0070] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0071] Example 1: Preparation of carbon-based confined bimetallic single-atom catalytic materials
[0072] (1) Preparation of precursor solution:
[0073] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and manganese acetate dihydrate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0074] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0075] The molar ratio of zinc nitrate, manganese acetate dihydrate, and 2-methylimidazole is 30:1:60.
[0076] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0077] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0078] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0079] (5) Introduction of the second metal: The dried carbon-based material was fully dispersed in 1000 ml of 50% isopropanol solution, and molybdenum chloride and melamine were added and mixed thoroughly. The mixture was ultrasonically dispersed for 2 h, filtered and recovered, and dried in a vacuum drying oven at 60 °C to constant weight. The particles were collected. The molar ratio of molybdenum chloride to melamine was 1:1~5.
[0080] (6) Secondary calcination: Under a nitrogen atmosphere, the particles obtained in step (5) are placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature is maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Mn-Mo-NC.
[0081] Figure 1 This is a scanning electron microscope image of the Mn-Mo-NC material.
[0082] Example 2: Preparation of carbon-based confined bimetallic single-atom catalytic materials
[0083] (1) Preparation of precursor solution:
[0084] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and copper acetate monohydrate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0085] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0086] The molar ratio of zinc nitrate, copper acetate monohydrate, and 2-methylimidazole is 10:1:60.
[0087] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0088] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0089] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0090] (5) Introduction of the second metal: The dried carbon-based material was fully dispersed in 1000 ml of 50% isopropanol solution, and molybdenum chloride and melamine were added and mixed thoroughly. The mixture was ultrasonically dispersed for 2 h, filtered and recovered, and dried in a vacuum drying oven at 60 °C to constant weight. The particles were collected. The molar ratio of molybdenum chloride to melamine was 1:1~5.
[0091] (6) Secondary calcination: Under a nitrogen atmosphere, the particles obtained in step (5) are placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature is maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Cu-Mo-NC.
[0092] Example 3: Preparation of carbon-based confined bimetallic single-atom catalytic materials
[0093] (1) Preparation of precursor solution:
[0094] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and nickel acetate tetrahydrate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0095] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0096] The molar ratio of zinc nitrate, nickel acetate tetrahydrate, and 2-methylimidazole is 10:1:30.
[0097] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0098] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0099] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0100] (5) Introduction of the second metal: The dried carbon-based material was fully dispersed in 1000 ml of 50% isopropanol solution, and molybdenum chloride and melamine were added and mixed thoroughly. The mixture was ultrasonically dispersed for 2 h, filtered and recovered, and dried in a vacuum drying oven at 60 °C to constant weight. The particles were collected. The molar ratio of molybdenum chloride to melamine was 1:1~5.
[0101] (6) Secondary calcination: Under a nitrogen atmosphere, the particles obtained in step (5) are placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature is maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Ni-Mo-NC.
[0102] Example 4: Preparation of carbon-based confined bimetallic single-atom catalytic materials
[0103] (1) Preparation of precursor solution:
[0104] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and molybdenum acetate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0105] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0106] The molar ratio of zinc nitrate, molybdenum acetate, and 2-methylimidazole is 20:1:40.
[0107] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0108] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0109] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0110] (5) Introduction of the second metal: The dried carbon-based material was fully dispersed in 1000 ml of 50% isopropanol solution, and molybdenum chloride and melamine were added and mixed thoroughly. The mixture was ultrasonically dispersed for 2 h, filtered and recovered, and dried in a vacuum drying oven at 60 °C to constant weight. The particles were collected. The molar ratio of molybdenum chloride to melamine was 1:1~5.
[0111] (6) Secondary calcination: Under a nitrogen atmosphere, the particles obtained in step (5) are placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature is maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Mo-Mo-NC.
[0112] Example 5: Preparation of carbon-based confined bimetallic single-atom catalytic materials
[0113] (1) Preparation of precursor solution:
[0114] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and manganese acetate dihydrate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0115] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0116] The molar ratio of zinc nitrate, manganese acetate dihydrate, and 2-methylimidazole is 30:1:60.
[0117] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0118] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0119] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0120] (5) Introduction of the second metal: The dried carbon-based material was fully dispersed in 1000 ml of 50% isopropanol solution, nickel chloride and melamine were added and mixed thoroughly, ultrasonically dispersed for 2 h, filtered and recovered, and dried in a vacuum drying oven at 60 °C to constant weight. The particles were collected. The molar ratio of nickel chloride to melamine was 1:1~5.
[0121] (6) Secondary calcination: Under a nitrogen atmosphere, the particles obtained in step (5) are placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature is maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Mn-Ni-NC.
[0122] Example 6: Preparation of carbon-based confined bimetallic single-atom catalytic materials
[0123] (1) Preparation of precursor solution:
[0124] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and manganese acetate dihydrate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0125] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0126] The molar ratio of zinc nitrate, manganese acetate dihydrate, and 2-methylimidazole is 10:1:20.
[0127] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0128] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0129] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0130] (5) Introduction of the second metal: The dried carbon-based material was fully dispersed in 1000 ml of 50% isopropanol solution, and manganese chloride and melamine were added and mixed thoroughly. The mixture was ultrasonically dispersed for 2 h, filtered and recovered, and dried in a vacuum drying oven at 60 °C to constant weight. The particles were collected. The molar ratio of manganese chloride to melamine was 1:1~5.
[0131] (6) Secondary calcination: Under a nitrogen atmosphere, the particles obtained in step (5) are placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature is maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Mn-Mn-NC.
[0132] Compare with Example 1
[0133] (1) Preparation of precursor solution:
[0134] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and manganese acetate dihydrate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0135] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0136] The molar ratio of zinc nitrate, manganese acetate dihydrate, and 2-methylimidazole is 30:1:60.
[0137] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0138] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0139] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0140] (5) Secondary calcination: Under a nitrogen atmosphere, the dried material was placed in a tube furnace and heated to 900°C at a rate of 5 °C / min. The temperature was maintained for 1.5 h to obtain a carbon-based confined bimetallic single-atom catalytic material, denoted as Mn-NC.
[0141] Compare with Example 2
[0142] (1) Preparation of precursor solution:
[0143] Take 500 ml of dimethylformamide as a solvent, add zinc nitrate and molybdenum acetate at room temperature, then place it in a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved to obtain solution A.
[0144] Using 500 ml of dimethylformamide as a solvent, add 2-methylimidazole at room temperature, then place the solution on a magnetic stirrer and stir at 800 rpm for 15 minutes until the solid is completely dissolved, yielding solution B.
[0145] The molar ratio of zinc nitrate, molybdenum acetate, and 2-methylimidazole is 20:1:40.
[0146] (2) Growth of nanocrystals: Under stirring, solution A was slowly added dropwise to solution B and mixed. Under sealed conditions, the mixture was kept at 120℃ for 25 h to promote the growth of nanocrystals with a metal Mn-nitrogen coordination structure. After the incubation period, the mixed solution was allowed to stand at room temperature to allow the nanocrystals to fully precipitate. The precipitate was centrifuged at 8000 r / min, 25℃, for 10 min, and the precipitate was collected. The precipitate was washed with anhydrous ethanol and placed in a vacuum drying oven to dry at 60℃ to constant weight to obtain nanocrystals.
[0147] (3) First calcination: Under a nitrogen atmosphere, the nanocrystals obtained in step (2) are placed in a tube furnace and heated to 1200℃ at a rate of 5℃ / min, and held for 1.5h.
[0148] (4) Pickling: Under stirring, disperse the material after one calcination in 0.5 M H2SO4 solution, pickle at 80℃ for 5 h, filter, wash the filter with at least 2 L of ultrapure water, and then place it in a vacuum drying oven at 60℃ to dry to constant weight.
[0149] (5) Secondary calcination: Under nitrogen atmosphere, the dried material is placed in a tube furnace and heated to 900℃ at 5℃ / min and held for 1.5h to obtain carbon-based confined bimetallic single-atom catalytic material, denoted as Mo-NC.
[0150] Verification experiment:
[0151] The catalytic materials obtained in Examples 1-5 and Comparative Examples 1 and 2, along with activated carbon, were used as catalysts to adsorb and remove perchlorate from drinking water. The specific steps included:
[0152] Step (1): Prepare 50 mL of perchlorate water sample with a concentration of 10 mg / L;
[0153] Step (2): Add 0.3 g / L of catalyst to the water sample prepared in step (1) and react at 1200 r / min using a stirrer. The reaction time is 300 s. The perchlorate content is measured, and the results are shown in Table 1.
[0154] The method for detecting perchlorate was as follows: perchlorate was analyzed using a Dionex ICS-600 ion chromatograph (Thermo Fisher Scientific, USA) with an AS19 (4 mm × 250 mm) analytical column and an AG 19 guard column (4 mm × 50 mm). The eluent was KOH and the flow rate of the eluent was 1 mL / min.
[0155] Table 1. Removal rate of perchlorate from drinking water by different catalysts
[0156]
[0157] The test results show that the carbon-based confined dual single-atom catalysts constructed in this invention can effectively remove perchlorate. Among them, the Mn-Mo-NC catalyst can achieve a removal rate of 78.23% of perchlorate in just 300 s, which is significantly higher than that of commonly used activated carbon adsorbents (only 5.11%).
[0158] Example 6 Parameter optimization experiment The Mn-Mo-NC catalytic material was prepared using the same method as in Example 1, except that the addition ratio of metal salt and ligand organic matter in steps (1) and (5) was different, and samples 1-3 were prepared respectively.
[0159] Samples 1-3 were used as catalysts to adsorb and remove perchlorate from drinking water, specifically including the following steps:
[0160] Step (1): Prepare 50 mL of perchlorate water sample with a concentration of 10 mg / L;
[0161] Step (2): Add 0.3 g / L of catalyst to the water sample prepared in step (1), and react at 1200 r / min using a stirrer. The reaction time is 300 s, and the perchlorate content is measured. The results are shown in Table 2. The results show that the ratio of metal salt to organic ligand significantly affects the characteristics of the catalyst, and thus the removal rate.
[0162] Table 2. Removal rate of perchlorate from drinking water by catalysts prepared with different addition ratios
[0163]
[0164] Example 7: Formic acid-enhanced removal of perchlorate from drinking water
[0165] Step (1): Prepare 50 mL of perchlorate water sample with a concentration of 10 mg / L;
[0166] Step (2): Add 0.3 g / L of Mn-Mo-NC prepared in Example 1 as a catalyst to the water sample prepared in Step (1), and simultaneously add formic acid of different concentrations. The reaction is carried out at 1200 r / min using a stirrer. The reaction time is 30 min, and the perchlorate content is measured.
[0167] Step (3): Place the remaining reaction solution from step (2) into a vacuum filtration device to recover the catalyst after the reaction;
[0168] Step (4): The recovered catalyst material was added to 50 mL of NaOH solution for elution. The chloride ion content in the elution product was measured after 30 min. The results are shown in Table 3.
[0169] Table 3. Effect of formic acid concentration on the removal of perchlorate from drinking water
[0170]
[0171] The results show that, on the one hand, the addition of formic acid further enhances the material's removal of perchlorate, mainly because formic acid strengthens the chemical adsorption of perchlorate. On the other hand, by adjusting the amount of formic acid used, the perchlorate removal process can be intensified, achieving the removal of nearly 98.23% of perchlorate. Further analysis of the elution products reveals that the catalyst can further reduce perchlorate to chloride ions.
[0172] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for removing perchlorate from drinking water, characterized in that: Using carbon-based confined bimetallic single-atom catalytic materials as catalysts; The catalytic material has a carbon base as a skeleton and nitrogen atoms as coordination atoms, and the metal atoms are dispersed and fixed in the form of single atoms through a metal-nitrogen coordination structure; the metal atoms are any combination of Mo-Mn, Mo-Cu, Mo-Ni, and Mo-Mo; The catalytic material is prepared by the following method: (1) Preparing a precursor solution: using dimethylformamide as a solvent, respectively preparing a solution A containing zinc nitrate and a first metal salt, and a solution B containing 2-methylimidazole; the first metal salt is one of manganese acetate dihydrate, copper acetate monohydrate, nickel acetate tetrahydrate, and molybdenum acetate; (2) Growing nanocrystals: mixing solutions A and B, keeping them warm under sealed conditions to promote the growth of nanocrystals with metal-nitrogen coordination structures, removing impurities by centrifugation and washing, and vacuum drying the precipitate to obtain nanocrystals; (3) Primary calcination: In a nitrogen atmosphere, the nanocrystals are heated to 900-1200°C for primary calcination; (4) Acid washing: The material after the primary calcination is subjected to acid washing, suction filtration, washing, and vacuum drying to obtain a carbon-based material; (5) Introduction of the second metal: fully dispersing the carbon-based material in an isopropanol solution, adding a second metal salt and melamine, ultrasonically dispersing, recovering, drying, and collecting particles; the second metal salt is molybdenum chloride; (6) Secondary calcination: In a nitrogen atmosphere, the particles are heated to 800-1000 °C for secondary calcination to obtain a carbon-based confined bimetallic single atom catalytic material.
2. A method for removing perchlorate from drinking water according to claim 1, characterized in that: The molar ratio of zinc nitrate, the first metal salt and 2-methylimidazole in step (1) is (10-30):1:(20-60).
3. A method for removing perchlorate from drinking water according to claim 1, characterized in that: In step (5), the molar ratio of the second metal salt to 2-methylimidazole is 1:(1-5).
4. According to a method for removing perchlorate in drinking water according to claim 1, when the carbon-based confined bimetallic single-atom catalytic material is used as a catalyst, it has a powdery, granular or carrier-loaded form.
5. A method for removing perchlorate from drinking water according to claim 4, characterized in that: The removal process is enhanced with formic acid.
6. A method for removing perchlorate from drinking water according to claim 4, characterized in that: The catalyst and a certain concentration of formic acid are sequentially added into a reactor containing the water sample to be purified, and the mixture is stirred sufficiently. The residence time of the water sample in the reactor is controlled to be 5 to 30 minutes, and then the mixture is filtered and the catalyst is recovered.
7. A method for removing perchlorate from drinking water according to claim 5, characterized in that: The concentration of formic acid is 0.5~2 mM.
Citation Information
Patent Citations
Oxygen reduction electrocatalyst of cobalt monatomic isolated platinum nanoparticles and preparation method of oxygen reduction electrocatalyst
CN115318322A
Method for controlling disinfection by-products in drinking water through catalytic ozonation
CN117645356A
Preparation method and application of molybdenum monatomic porous carbon
CN117942966A
Method for preparing laminar zinc hydroxide organic-inorganic nanocomposites for use in the removal and degradation of dyes from textile effluents
US20190193061A1